Portrait of Social Life in Fiction (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the role of fiction in reflecting social life, its impact on the development of society, social consciousness and cultural processes. The principles of the writer's re-creation of the reality of life through artistic interpretation, the system of images, conflict, plot and sociality based on artistic details are interpreted. Also, the traditions of portraying social life in Eastern and Western literature are covered in a comparative approach.